Vaccine-Induced CD8+ T Cell Responses in Children: A Review of Age-Specific Molecular Determinants Contributing to Antigen Cross-Presentation - Beijnen, Elisabeth M. S.; van Haren, Simon D. (Frontiers in Immunology, 2020)
Infections are most common and most severe at the extremes of age, the young and the elderly. Vaccination can be a key approach to enhance immunogenicity and protection against pathogens in these vulnerable populations, who have a functionally distinct immune system compared to other age groups. More than 50% of the vaccine market is for pediatric use, yet to date vaccine development is often empiric and not tailored to molecular distinctions in innate and adaptive immune activation in early life. With modern vaccine development shifting from whole-cell based vaccines to subunit vaccines also comes the need for formulations that can elicit a CD8+ T cell response when needed, for example by promoting antigen cross-presentation. While our group and others have identified many cellular and molecular determinants of successful activation of antigen-presenting cells, B cells and CD4+ T cells in early life, much less is known about the ontogeny of CD8+ T cell induction. In this review, we summarize the literature pertaining to the frequency and phenotype of newborn and infant CD8+ T cells, and any evidence of induction of CD8+ T cells by currently licensed pediatric vaccine formulations. In addition, we review the molecular determinants of antigen cross-presentation on MHC I and successful CD8+ T cell induction and discuss potential distinctions that can be made in children. Finally, we discuss recent advances in development of novel adjuvants and provide future directions for basic and translational research in this area.